Humanism and New Atheism: experiences and proposals of an educational minority - Bandini, Gianfranco (Historia y Memoria de la Educación, 2020)
The research intends to trace a profile of two twentieth-century movements — Humanism and New Atheism — which, from an educational point of view, constitute an interesting and original minority. Although both studies and activities of undeniable educational interest have been produced, they have not yet been put at the centre of specific research. They currently represent one of the most innovative aspects of the current debate on the purpose of education both at school and in the family. These are movements that are not only academic or theoretical research, but they represent a varied social sample which in some countries, moreover, is no longer a small minority, but clearly affects public opinion and even parts of the political agenda. The analysis of the recent history of movements that we can define of an “atheist world” indicates a clear trend line: their positions seem destined to be an integral part of the debates on current educational issues, particularly because the positions they expressed — with their constant anchoring to scientific culture and rational dialogue — seem suitable to face the difficult challenges of globalisation and the tensions that cross pluralistic societies.